Investigating the impact of calcium presence in dairy wastewater on struvite precipitation - Sinno, Sarah Samir (2022)
A Master of Science thesis in Civil Engineering by Sarah Samir Sinno entitled, “Investigating the impact of calcium presence in dairy wastewater on struvite precipitation”, submitted in December 2022. Thesis advisor is Dr. Kazi Parvez Fattah. Soft copy is available (Thesis, Completion Certificate, Approval Signatures, and AUS Archives Consent Form).